Design of advanced multicomponent ferroelectric liquid crystalline mixtures with submicrometre helical pitch. Issue 4 (16th March 2017) - Kurp, Katarzyna; Czerwiński, Michał; Tykarska, Marzena; Bubnov, Alexej
ABSTRACT: New functional multicomponent ferroelectric liquid crystalline mixtures have been designed while searching smart self-assembling materials with submicrometre periodicity of the helical structure responding definite demands for application in electro-optic devices and photonics that exploit the deformed helix ferroelectric effect. The resulting designed mixtures possess the paraelectric smectic A* and the tilted ferroelectric smectic C* phases over a very broad temperature range down below the room temperature. The mesomorphic, electro-optic and dielectric properties have been studied and discussed. The presence of a very stable enantiotropic ferroelectric smectic phase exhibiting almost temperature independent helical pitch within 150–250 nm range and reasonably high values of the tilt angle might allow these mixtures to be applicable for practical purposes. GRAPHICAL ABSTRACT: